Punishing criminals indigenously: Perspectives from customary law and social relationship practices of Afar pastorals along the Lower Awash Valley - Bisrat Teklesilassie Yazew; Getachew Kassa (Cogent Social Sciences, 2023)
AbstractThis research provides an overview of the application and practices of cultural values and customary law in preventing and correcting violations of norms and regulations, i.e. criminal acts. A qualitative approach with deep interviews, focused group discussions, and situational observations was applied, and the data was analyzed using the thematic interpretation technique. It was discovered that Digalla helped to balance the socio-cultural structures of the Afars’ way of life. Some of the significant challenges that the Afar are facing include occasional disputes between statutory law, Islamic Sharia, customary law, and state-imposed law, difficulties faced by traditional courts in enforcing their decisions, differing opinions on whether and how to record and codify indigenous customary law, and the erosion of customary law principles and practices by the current generation. It is suggested that many the non-adversarial cultural values and customary law practices in penal or reform measures may offer models for possible replication within mainstream justice and penal systems of other social groups in the country in general.